A national snapshot of early-career secondary school music teachers : Engagement, obstacles and support - Robinson, Jennifer (Australian journal of music education, 2020)
Early-career teachers are referred to in the literature as being in their first few years of teaching experience (Ballantyne and Zhukov, 2017; Dabback, 2018). This research aims to identify current issues that affect the aspirations of early-career secondary school music teachers, including what motivates and engages them in their work and what impedes their progress in the profession. This paper reports findings from a national survey that is part of a larger qualitative study. The survey was sent to over 500 secondary school music teachers across the states and territories of Australia. The survey, containing a mixture of Likert-type and open-ended questions, covered areas such as motivation, stress, value, challenge, professional development, work/life balance and career goals. Of the 263 responses, 59 were from early-career secondary school music teachers across Australia. This research revealed that, while enjoyment of teaching was a strong motivator, teachers' sense of belonging to the school culture was enhanced by having their subject valued and being professionally acknowledged. Early-career secondary school music teachers are having some success finding worthwhile and skill-enhancing professional development, but accessibility and meeting career need are overriding issues. The research also indicates that these teachers are encountering an inconsistent approach to the implementation of the Australian Arts Curriculum across the states and territories. Early-career secondary school music teachers also struggle with work/life balance. Despite these difficulties, these teachers have a positive outlook and future goals for their careers as music educators. This paper provides suggestions for professional development for this career stage and gives insight into the work/life balance and career forecast for these music teachers. It informs school leaders in their support and valuing of these teachers and their subject. [Author abstract]